Effect Of Service Quality And Employee Performance On Customer Satisfaction at PT. Pawnshop Pinang City Sharia Service Unit - aisyah pratiwi; muhammad isa; ali hardana; sulaiman efendi (Journal Of Sharia Banking, 2022)
Customer satisfaction is a level where the needs, desires and expectations can be met. This research is motivated by the lack of services provided by employees to customers so that there are some customers who are not satisfied. Inadequate employee performance so that there are multiple roles in carrying out tasks and become less than optimal. This study aims to determine the effect of service quality and employee performance at PT. Pawnshops of the Syariah Service Unit of the City of Pinang. The theories that support this research consist of understanding customer satisfaction, methods for measuring customer satisfaction, strategies to increase satisfaction, factors that affect satisfaction, understanding service quality, dimensions of service quality, understanding performance, employee performance indicators, factors that affect employee performance. The method used in this research is quantitative. Data collection techniques using a questionnaire.Sampling in this study using incidental sampling with a sample of 96 people. The tests used include descriptive analysis, instrument testing (validity test, reliability test), classical assumption test (normality test, multicollinearity test, autocorrelation test, heteroscedasticity test), hypothesis testing (R2 test, t test, F test), multiple linear regression analysis , assisted by the SPSS 23 program. The results of the partial study indicate that the service quality variable has a positive effect on customer satisfaction. Employee performance variable has no positive effect on customer satisfaction. Meanwhile, simultaneously the variables of service quality and employee performance have a positive effect on customer satisfaction. While the coefficient of determination (R2) test is obtained a value of 0,407 or 40,7%, this shows that the quality of service and employee performance on customer satisfaction is 40,7% .While the remaining 59,3% is influenced by other variables not included in this study.